Formulasi Sediaan Krim Anti Acne dan Uji Aktivitas Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb) terhadap Propionibacterium acnes - Syahrida Dian Ardhany; Yunari Puspitasari; Yuyun Meydawati; Susi Novaryatiin (Jurnal Sains dan Kesehatan, 2019)
Bawang dayak (Eleutherine bulbosa (Mill.)urb) is one of plants of Central Kalimantan. Empirically, Bawang dayak is used to treat skin problems, one of them is acne vulgaris, so that it is necessary to test the inhibition of ethanolic extract of Bawang Dayak against acne causing such as P.acnes. In the pharmaceutical world there is still no research conducted on the manufacture of antiacne cream contain ethanolic extract of Bawang Dayak bulbs, so the researchers conducted it to improve the efficiency of the use of traditional medicine. The results of phytochemical screening showed that ethanolic extract of bawang dayak contained flavonoid, alkaloid, saponin, tanin and catechol with the inhibition zone classified as moderate activity at the concentration of 1% and weak activity at other concentrations (5%, 10% and 15%). Based on the evalution of cream preparations the results of the organoleptic test for antuacne cream have a dark brown color and distinctive odor, homogen for homogeneity test, adhesion test and dispersion test according to the requirements and the pH observation showed ph (6) suitable for topical application. Based on these results, the evaluation antiacne cream fulfills the physical test, but it needs to be developed further for stability and effectiveness of antiacne cream against the bacteria acnes causing.